Tissue ischemia time affects gene and protein expression patterns within minutes following surgical tumor excision - Annika Spruessel; Garnet Steimann; Mira Jung; Sung A. Lee; Theresa Carr; Anne-Kristin Fentz; Joerg Spangenberg; Carsten Zornig; Hartmut H. Juhl; Kerstin A. David (BioTechniques)
The aim of this study was to determine the impact of ischemia on gene and protein expression profiles of healthy and malignant colon tissue and, thus, on screening studies for identification of molecular targets and diagnostic molecular patterns. Healthy and malignant colon tissue were snap-frozen at various time points (3–30 min) after colon resection. Gene and protein expression were determined by microarray (HG-U133A chips) and surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF MS) technology (CM10 chips, SAX2 chips, and IMAC3Ni chips), respectively. Real-time reverse transcription PCR (RT-PCR) was used for comparative measurement of expression of particular genes. Initial changes of gene and protein expression profiles were already observed 5–8 min after colon resection. Fifteen minutes after surgery, 10%–15% of molecules, and after 30 min, 20% of all detectable genes and proteins, respectively, differed significantly from the baseline values. Significant changes of expression were found in most functional groups. As confirmed by real-time RT-PCR, this included not only known hypoxia-related molecules (HIF-1α, c-fos, HO-1) but also cytoskeletal genes (e.g., CK20) and tumor-associated antigens (e.g., CEA). In conclusion, preanalytical factors, such as tissue ischemia time, dramatically affect molecular data. Control of these variables is mandatory to obtain reliable data in screening programs for molecular targets and diagnostic molecular patterns.